2022
DOI: 10.3390/w14132027
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Networks for the Prediction of the Reference Evapotranspiration of the Peloponnese Peninsula, Greece

Abstract: The aim of the study was to investigate the utility of artificial neural networks (ANNs) for the estimation of reference evapotranspiration (ETo) on the Peloponnese Peninsula in Greece for two representative months of wintertime and summertime during 2016–2019 and to test if using fewer inputs could lead to satisfactory predictions. Datasets from sixty-two meteorological stations were employed. The available inputs were mean temperature (Tmean), sunshine (N), solar radiation (Rs), net radiation (Rn), vapour pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 84 publications
1
6
0
Order By: Relevance
“…In contrast, the full inputs involving Tmin, Tmax, Ra, and MN generally perform the best. The studies by Dimitriadou and Nikolakopoulos [39,40] also found similar results. They applied multiple linear regression and ANN for predicting ET0 of the Peloponnese Peninsula, Greece.…”
Section: Discussionsupporting
confidence: 66%
“…In contrast, the full inputs involving Tmin, Tmax, Ra, and MN generally perform the best. The studies by Dimitriadou and Nikolakopoulos [39,40] also found similar results. They applied multiple linear regression and ANN for predicting ET0 of the Peloponnese Peninsula, Greece.…”
Section: Discussionsupporting
confidence: 66%
“…It was found that, mostly in August, (wind speed is generally very low in summer), in cases where increased u 2 values occurred, ETo was directly affected. This deduction is confirmed by the latest study on ETo across the Peloponnese, in which u 2 was proven to be the most influential parameter after Tmean [73]. In conclusion, it is probable that the relationship between u 2 and ETo is non-linear, thus the MLR model would not depict the established relationship.…”
Section: Discussionmentioning
confidence: 83%
“…In other words, MLR aims to find the linear function that minimizes the sum of the squares of errors (SSE) between the observed and the predicted data. An advantage of this method is the easy interpretation of the coefficients, which are generated in the model with low computational effort, in comparison to more complex techniques, such as energy balance methods and artificial intelligence algorithms [13][14][15][16][17][18][19][20][21][24][25][26][27][28][29][30][37][38][39][40][41][42][43][67][68][69][70][71][72][73][74][75]. For the MLR model, the response (dependent) variable y is assumed to be a function of k independent variables x i .…”
Section: Methodsmentioning
confidence: 99%
“…Dimitriadou and Nikolakopoulos [31] evaluate the performance of the Artificial Neural Network (ANN) for the Peloponnese Peninsula in Greece. The dataset comprising of mean temperature (Tmean), sunshine (N), solar radiation (Rs), net radiation (Rn), vapor pressure deficit (es-ea), wind speed (u2), and altitude (Z) from the year 2016 to 2019 for sixty-two weather stations.…”
Section: Literature Reviewmentioning
confidence: 99%